PENGARUH TEH DAUN KALAKAI (STENOCHLAENA PALUSTRIS) TERHADAP KADAR HEMOGLOBIN PADA REMAJA PUTRI ANEMIA - Putri, Dian Purnama; Pujiastuti, Rr Sri Endang; Ramlan, Djamaluddin (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2022)
Abstract: Adolescents are the next generation of the nation but there are many problems experienced by adolescents in Indonesia, namely iron deficiency (anemia), stunting, chronic lack of energy, and obesity. The prevalence of anemia incidence increases every year, Riskesdas data shows the prevalence of anemia in young women in Indonesia in 2013 was 37.1%, and in 2018 there was a fairly high increase of 48.9%, so that the greater the impact that occurs on adolescent women anemia such as physical growth and adolescent mental health. One way to deal with anemia is to use kalakai leaf plants which are used as tea. Kalakai leaf tea contains iron, vitamin C, vitamin A, and protein that serves to raise hemoglobin levels. The purpose of this study was to determine the effect of Kalakai leaf tea (Stenochlaena palutris) on haemoglobin levels in young women who had anemia. The research method uses a quasi-experimental method with a pretest posttest design with control group design. The results showed that there was an influence of hemoglobin levels before and after treatment with a p-value of 0.000. There were differences in hemoglobin levels in the intervention group and the control group in anemic young women with a p-value of 0.034. In the intervention group increased hemoglobin levels by 19.6% and the control group by 14.67%. The conclusion of this study is that there is an influence before and after the administration of kalakai leaf tea (Stenochlaena palutris) on hemoglobin levels in anemic young women.Abstrak: Remaja merupakan generasi penerus bangsa namun banyak permasalahan yang dialami remaja di Indonesia yaitu kekurangan zat besi (anemia), stunting, kurang energi kronis (KEK), dan obesitas. Prevalensi kejadian anemia meningkat setiap tahunnya, data Riskesdas menunjukkan prevalensi anemia pada remaja putri di Indonesia pada tahun 2013 sebesar 37,1%, dan pada tahun 2018 terjadi peningkatan yang cukup tinggi yaitu mencapai 48,9%, sehingga semakin besar dampak yang terjadi pada remaja putri anemia seperti pertumbuhan fisik dan kesehatan mental remaja. Salah satu cara dalam menangani anemia yaitu menggunakan tumbuhan daun kalakai yang dijadikan teh. Teh daun kalakai memiliki kandungan zat besi, vitamin C, vitamin A, dan protein yang berfungsi untuk menaikkan kadar hemoglobin. Tujuan penelitian ini adalah untuk mengetahui pengaruh teh daun Kalakai (Stenochlaena palutris) terhadap kadar haemoglobin pada remaja semu atau quasi eksperiment dengan rancangan pretest posttest with control group design. Hasil penelitian menunjukkan bahwa terdapat pengaruh kadar hemoglobin sebelum dan sesudah diberikan perlakuan dengan p-value 0.000. terdapat perbedaan kadar hemoglobin kelompok intervensi dan kelompok control pada remaja putri anemia dengan nilai p-value 0.034. pada kelompok intervensi peningkatan kadar hemoglobin sebesar 19,6% dan kelompok kontrol 14,67%. Kesimpulan penelitian ini adalah ada pengaruh sebelum dan sesudah pemberian teh daun kalakai (Stenochlaena palutris) terhadap kadar hemoglobin pada remaja putri anemia.